Behavioral Differences In Seeking Help For Mental Health Among Generation Z From The Kodi People Group And The Madurese Ethnic Group - Yohanis Dodok; Ahmad Guntur; Indriyawati; Kurniawan Erman Wicaksono (Chakra Brahmanda Lentera Institute, 2022)
Background: mental health problems in generation Z of the Kodi People Group and Madurese ethnic group in their behavior in seeking mental health assistance. The purpose of this study is to analyze the differences in the behavior of mental help seeking from Generation Z in the Kodi people group and Madurese ethnic group. Methods: This research used quantitative research method, namely, the survey method. The subjects of this study were Generation Z from the Kodi people group and the Madurese who have experienced mental health problems such as stress, anxiety, depression, suicidal thought, drug use, and physical illness. The sampling technique used was purposive sampling with a total of 200 respondents from Generation Z. This study used the instrument of General Help-Seeking Questionnaire Vignette Version (GHSQ-V). The hypothesis test in this study was a paired t-test. Results: 33% of respondents from the Kodi people group had behavior in seeking mental health assistance that was categorized as